Pentingnya Berpikir Ilmiah dalam Konseling Pastoral: Integrasi Epistemologis untuk Praktik yang Reflektif dan Bertanggung Jawab - Anto Wahyu Prastyo, Andri; Rahayu, Susi (JOURNAL of THEOLOGICAL STUDENTS, 2025)
Traditional pastoral counseling often relies on intuition or spiritual experience without a systematic methodological foundation, making it difficult to measure intervention effectiveness and limiting accountability in service. This study aims to explore the importance of scientific thinking in pastoral counseling practice as a means of epistemological integration between psychology and spirituality, to produce reflective and responsible practice. The method employed includes a literature review on counseling theories, scientific epistemology, and pastoral practice, as well as conceptual analysis on the application of scientific methodology in assessment and counseling interventions. The results indicate that applying scientific thinking enables pastoral counselors to evaluate intervention effectiveness objectively, reduce subjective bias, and strengthen professional service. Integrating scientific approaches with spiritual values also allows counselors to facilitate clients’ holistic growth, uniting psychological, social, and spiritual aspects. Thus, an ideal pastoral counselor functions as both a spiritual guide and a reflective scholar grounded in validated data, theory, and experience.